Impact of Irritable Bowel Syndrome upon Female s' Health Related Quality of Life (Baghdad Science Journal, 2025)
Irritable bowel syndrome (IBS) is a highly prevalent gastrointestinal disorder characterized by abdominal pain with diarrhea and/or constipation. The morbidity records reveal large differences per 1000 patients per year, the incidence varies from 4-13 % and the prevalence from 6-20 % and that the syndrome is more prevalence among women than among men, it is occurs mainly between the ages of 15 and 65 and often causes long- term complications. Its about 15-20% in women the etiology of IBS has not been definitively established. It was originally thought to be a psychosomatic disorder, but more recent studies have identified chronic immune activation. The impact of IBS upon humans is tremendous. Chronic and recurring symptoms of IBS can disrupt personal and professional activities, upset emotional well-being and limit individual potential. It is imperative that the best ways to manage and treat this syndrome are made available to patients so they can enjoy a normal and healthy life.Descriptive analytical design of the study starting from July 8th 2008 to the April 29th 2009 in order to identify the impact of IBS upon Health Related Quality of Life at females.The present study was carried out in the Gastroenterology and Liver Disease Hospital (G&LDH) in Baghdad.A non- probability (purposive) sample of 100 adults females who have IBS.The questionnaire was composed of two parts and introductory page that invite the subjects to participate in the study.Part I: Socio- Demographic Information Sheet Part II: Used Short-form 36 Items version II, (Standard Version of WHO for quality of life) which included: (Health status, Physical function, Role physical, Role emotion, Social function, Bodily Pain, Vitality, Mental health, and General health).The findings of (100) IBS females of present study Indicated that the(30%) at 28-37 years old, (54%) continuous married , most of them (61%) were government employee, Majority of sample ( 42%) were college graduate, half of the sample were high level income, and the females complain from alternate between constipation and diarrhea were 47%. The total means of role physical and role emotion were lower than total means for other domains of Health Related Quality of life.A negative impact of IBS on Health Related Quality of life in females at 28-37years, widow were lowered quality of life, the IBS were negative impact on government employed females.